EFFECT OF ASCORBIC ACID ON FATIGUE OF SKELETAL MUSCLE FIBRES IN LONG TERM COLD EXPOSED SPRAGUE DAWLEY RATS - Rashid, Aneeqa; Khan, Umar Ali; Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: On exposure to prolonged cold temperature, the body responds for effective heat production both by shivering and non-shivering thermogenesis. Cold exposure increases the production of reactive oxygen species which influence the sarcoplasmic reticulum Ca++ release from the skeletal muscles and affect their contractile properties. The role of ascorbic acid supplementation on force of contraction during fatigue of cold exposed skeletal muscles was evaluated in this study. Method: Ninety healthy, male Sprague Dawley rats were randomly divided into three groups of control (I), cold exposed (II), and cold exposed with ascorbic acid 500 mg/L supplementation mixed in drinking water (III). Group II and III were given cold exposure by keeping their cages in ice-filled tubs for 1 hr/day for one month. After one month, the extensor digitorum longus muscle was dissected out and force of contraction during fatigue in the skeletal muscle fibres was analysed on a computerised data acquisition system. Results: The cold exposed group showed a significant delay in the force of contraction during fatigue of skeletal muscle fibres compared to control group. Group III showed easy fatigability and a better force of contraction than the cold exposed group. Conclusions: Ascorbic acid increases the force of contraction and decreases resistance to fatigue in the muscles exposed to chronic cold. Keywords: Ascorbic acid, cold stress, fatigue, skeletal muscles